An exploration of healthcare providers' experiences and perspectives of Traditional and complementary medicine usage and disclosure by Indigenous cancer patients - A. Gall; K. Anderson; J. Adams; V. Matthews; G. Garvey (BMC, 2019)
Abstract Background Traditional and complementary medicines (T&CM) are any form of medicine, practice, treatment, product, technology, knowledge system or ceremony outside of conventional medical practice that aims to prevent and/or treat illness and/or promote well-being. Alongside conventional cancer treatments, T&CM usage is increasing; with 19% of indigenous Australians with cancer reporting using T&CM. There is limited evidence surrounding T&CM use and disclosure by indigenous patients. Our aim was to explore healthcare providers' views about usage, disclosure/non-disclosure of T&CM by Indigenous cancer patients. Methods Semi-structured, in-depth interviews with 18 healthcare providers, including three indigenous providers, at a large urban hospital providing care to Indigenous cancer patients were conducted to explore providers' experiences and attitudes towards T&CM use by Indigenous cancer patients. An interpretive phenomenological approach was used to thematically analyse the data. Results Analysis revealed six themes: concern about risk; no 'real' benefits; perception of T&CM and conventional medicine as antithetical; barriers to disclosure; 'patients' choice' a double-edged sword; and providers' lack of knowledge about T&CM. Healthcare providers perceived discord between T&CM and conventional medicine. Most lacked knowledge of T&CM, and had concerns around negative-interactions with conventional treatments. They considered T&CM outside their role, citing this as reasoning for their lack of knowledge. Indigenous healthcare providers had greater understanding and openness towards T&CM. Conclusions Given the potential usage of T&CM by Indigenous cancer patients, providers need a more comprehensive understanding of T&CM in order to inform discussion and facilitate effective disclosure on this topic. If indigenous Australians with cancer feel that cancer care providers are unreceptive to discussing T&CM, patient care risks being compromised; particularly given the potential for negative interactions between T&CM and conventional cancer treatments. Fostering health care interactions where indigenous patients feel comfortable to discuss T&CM usage should be a priority for all cancer care services.